Anti-depressant medication use is a risk factor for incident knee surgery and opioid use in patients with knee osteoarthritis - Zheng, Yongqiang; Zhang, Jinshan; Wang, Zefeng; Liu, Xiaofeng; Xu, Yongquan; Fang, Yangzhen; Lin, Zhenyu; Lin, Liang (Frontiers in Psychiatry, 2023)
Objective To investigate whether depression and exposure of antidepressant medication are independent risk factors for incident knee surgery and opioid use in knee osteoarthritis (KOA) patients.We identified all patients who visited our outpatient department with clinically diagnosed with KOA between January 2010 and January 2018. We retrieved their demographic, clinical and radiographic data from the database of our hospital. Next, we analyzed the effect of depression and anti-depressant medication on the incident knee surgery and opioid use in KOA patients.Results A total of 4341 KOA patients were found eligible to form the study population. Incident knee surgery and opioid use in purpose of treating osteoarthritis was observed in 242 and 568 patients, respectively.Incident knee surgery was significantly associated age (OR [95%CI],1.